2020
DOI: 10.1002/adma.202003137
|View full text |Cite
|
Sign up to set email alerts
|

Ruddlesden–Popper‐Phase Hybrid Halide Perovskite/Small‐Molecule Organic Blend Memory Transistors

Abstract: Controlling the morphology of metal halide perovskite layers during processing is critical for the manufacturing of optoelectronics. Here, a strategy to control the microstructure of solution‐processed layered Ruddlesden–Popper‐phase perovskite films based on phenethylammonium lead bromide ((PEA)2PbBr4) is reported. The method relies on the addition of the organic semiconductor 2,7‐dioctyl[1]benzothieno[3,2‐b]benzothiophene (C8‐BTBT) into the perovskite formulation, where it facilitates the formation of large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…[ 247 ] Anthopoulos et al adopted a blending method to incorporate small molecule materials into the preparation of perovskite/small molecule bilayers (Figure 13b). [ 248 ] By adjusting the ratio of (PEA) 2 PbBr 4 and C8‐BTBT, the spontaneous formation of platelet‐like domains of 2D‐(PEA) 2 PbBr 4 was realized by one‐step solution process. The quantum wells formed on the interface played a role of floating‐gate, which could capture the holes.…”
Section: Btbt Derivatives‐based Devicesmentioning
confidence: 99%
“…[ 247 ] Anthopoulos et al adopted a blending method to incorporate small molecule materials into the preparation of perovskite/small molecule bilayers (Figure 13b). [ 248 ] By adjusting the ratio of (PEA) 2 PbBr 4 and C8‐BTBT, the spontaneous formation of platelet‐like domains of 2D‐(PEA) 2 PbBr 4 was realized by one‐step solution process. The quantum wells formed on the interface played a role of floating‐gate, which could capture the holes.…”
Section: Btbt Derivatives‐based Devicesmentioning
confidence: 99%
“…This positive development is also accompanied by an overall improvement of device performance, illustrated by the gradual increase in mobility and the emergence of perovskite-based FETs with novel functionalities such as memory. [180,185] Still, many other challenges remain to be addressed, in particular, issues related to device stability, where significantly more research is required.…”
Section: Summary and Future Opportunitiesmentioning
confidence: 99%
“…In this 2D Ruddlesden‐Popper perovskite, the lead bromide layers separated by the insulating organic cations acted as floating gate and allowed effective trapping/de‐trapping of holes depending on the applied gate voltage. [ 185 ] The authors demonstrated stable performance after over 10 000 read/write cycles with a high operating window. Retention times exceeded 55 000 s and the switching ratio were always above 10 4 .…”
Section: Current Status In Perovskite Transistors and Phototransistorsmentioning
confidence: 99%
“…Because of their wide spectral range of optoelectronic responsiveness, flexibility, and vast area processability, OSCs are interesting options for manufacturing high-performance optoelectronic devices and circuits [33,[40][41][42][43]. Reducing the thickness of organic crystals to a few layers or even a single monolayer improves performance in a variety of ways: (i) reduce contact resistance and Schottky barrier so that an ohmic contact can be achieved, as depicted in figures 2(c) and (d) [44][45][46][47], (ii) increase carrier mobility, as shown in figures 2(a) and (b) [45,[48][49][50][51][52][53][54][55][56], and (iii) achieve controllable growth [57]. Apart from the electrical advancements of transistors, obvious enhancement of internal photo-response in the application of 2D OCs-based optoelectronic transistor compared with that of the same bulk crystals, as shown in figures 2(e) and (f) [48].…”
Section: Promises Of 2d Organic Crystalsmentioning
confidence: 99%